Intra-lesional NSAIDs Injection: Unreported Treatment in (Extra-abdominal) Desmoid Tumors. - Siriwittayakorn, Wuttipong; Apornchayanon, Olarn; Lorsomradee, Sratwadee; Theera-Umpon, Nipon; Settakorn, Jongkolnee; Pruksakorn, Dumnoensun (The Bangkok Medical Journal, 2016)
Desmoid tumors are a rare benign tumor that can be locally aggressive and causemorbidity to a patient. The best way of treatment, whether surgical or non-surgical, hasyet to be found. We report an unreported method of treatment in (extra-abdominal)desmoid tumor which showed a positive result. Our patient presented with (extraabdominal)desmoid tumor on her left forearm that caused her pain and paresthesia inthe left forearm. The mass was located near an important neurovascular structure makingthe authors opt for conservative management. Desmoid tumor cells show expressionof COX-2 and beta-catenin. NSAIDs the COX enzyme inhibitors are used orally toconservatively treat (extra-abdominal) desmoid tumor. To our knowledge, NSAIDshave never been used locally. Here we report our treatment of (extra-abdominal)desmoid tumor by injecting NSAIDs directly into the tumor and follow up on theclinical and radiographic study of the patient. This diversion of treatment, which hadnever been done before, showed a positive outcome in decreasing symptoms and sizeof the tumor in our patient. In this reported case, local NSAIDs injection into (extraabdominal)desmoid tumor showed a positive result. We hope this case report can leadto a further study of this way of treatment and we hope that this report could be a pathto a further study for the cure of desmoid tumors.